Powerful Silence as a Decolonizing Writing Strategy in Maria Dermoût’s De juwelen haarkam - van Engelenhoven, Gerlov (FRAME, Journal of Literary Studies, 2026)
In this article, I analyze Maria Dermoût’s short story De juwelen haarkam (“The Jeweled Hair Comb”), a literary retelling of an anticolonial revolt that took place in the Dutch East Indies in 1817. I argue that Dermoût’s use of silence in this story is a decolonizing writing strategy used to disrupt the authority attached to the colonial voices that have shaped the current-day collective memory of this event. By finding ways to replace dominant historical voices with forms of indeterminate silence, Dermoût rewrites history not by forcing her own voice upon it, but instead by granting it silence, which allows for the anti-colonial resistance to be remembered differently. This article thus offers a critical reassessment of the logocentrism evident in much cultural theory and activism, in which ‘voice’ is reduced to a metaphor for empowerment and ‘silence’ to its negative counterpart, indicating powerlessness. My reading of Dermoût’s work shows how silence itself can be powerful.